Content Analysis of Iqra' Book for Arabic Learning According to Krippendorff's Perspective - Khitom, Khusnul; Bahy, Moh. Buny Andaru (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2023)
This research examines the material content of Iqra' book volumes 1 to 6, published by the National LPTQ Research Center